Correlation between Testicular Morphometric Parameters and Sperm Reserves in Ghanaian West African Dwarf Rams - Joseph Atawalna; Daniel Cobbinah Junior Essel; Nicholas Nettey; Patrick Mensah Amponsah (Veterinary Medicine International)
The current study was conducted to investigate the association between testicular morphometric parameters and sperm reserves in Ghanaian West African Dwarf rams. The intact scrotum along with testes and epididymides from twelve rams were collected immediately after slaughtering and transported to the Regional Veterinary Laboratory. The left testes and epididymides from all rams were dissected and the testes were individually weighed. The individual length, width, and volume of the testis and cauda epididymis were determined. Tissue samples were taken from testicular parenchyma, homogenized, and used to determine gonadal sperm concentration using a hemocytometer. Spermatozoa were recovered from the cauda epididymis by the incision method and used to determine the spermiogram. The weight, length, width, and volume of the testis were 63 ± 11 gram, 6.7 ± 0.44 cm, and 4.6 ± 0.40 and 74 ± 19 cm3, respectively, while the same parameters (except weight) for the cauda epididymis were 3.2 ± 0.35 cm, 1.8 ± 0.16 cm, and 5.48 ± 1.5 cm3, respectively. The sperm reserves per testis (SR), sperm reserves per gram testis (SRG), daily sperm production per testis (DSP), and daily sperm production per gram testis (DSPG) were (11,740 ± 386, 250 ± 6, 2350 ± 7.7, and 50 ± 1.0) million sperm cells, respectively. The cauda epididymal sperm reserves were 1,386 ± 456 million sperm cells, and the sperm motility (M%), morphologically normal viable cells (N%), dead sperm cells (D%), and morphologically abnormal sperm cells (A%) were 89 ± 3.2, 70.13 ± 8.0, 13.55 ± 5.05, and 16.33 ± 7.9, respectively. In conclusion, testicular morphometric parameters in Ghanaian West African Dwarf rams are highly and positively correlated (r = 0.7487–0.9354) with sperm reserves and production.